Grammaticalization, Lexicalization, and Frequency: Evidence from Clitics - C. Bennett, David (Slavia Centralis, 2020)
The paper treats the problem of clitic ordering in Slovene, Bosnian/Croatian/Serbian and other Slavic languages, attempting to find an underlying mechanism for the progression of change. The author discusses grammaticalization and lexicalization as motivations for the progression. The work, which is the authors last, remains unfinished.